Anesthetic protocol using propofol and isoflurane in spectacled bear (Tremarctos ornatus) - Pereira Júnior, Júlio Rodrigues; Macêdo, Marília Gabryelle Guimarães de; Henrique, Fernanda Vieira; Farias, Roberto Citelli; Neri; Thiago Ferreira Lopes; Menezes, Flávia Ferreira de (Brazilian Journal of Veterinary Research and Animal Science, 2023)
The management of wild animals generally requires chemical containment with the use of sedatives, tranquilizers, general anesthetics or dissociative drugs. The spectacled bear (Tremarctos ornatus) is the only member of the family Ursidae characteristic of South America. There are few reports on the main anesthetic protocols used in this specie. The aim of the present study was to report the use of propofol and isoflurane in a captive spectacled bear, after sedation with tiletamine-zolazepam. A male bear approximately 15 years old and 264 lb (scale weight) underwent anesthesia for treatment of a recurrent ulcerated wound on the neck. A combination of tiletamine and zolazepam injected intramuscularly was initially used. Due to the need to prolong the anesthetic time, the decision was made to administer propofol 1% (4.0 mg/kg/IV), which proved satisfactory regarding the inhibition of eyelid and laryngotracheal reflexes, thereby facilitating tracheal intubation. The subsequent use of isoflurane provided adequate maintenance of anesthesia, with vital signs within the normal range for the species, but there was hyperthermia. Based on the present findings, the use of tiletamine/zolazepam, propofol and isoflurane proved satisfactory and the doses employed were safe for the spectacled bear (Tremarctos ornatus). Inhalation anesthesia was essential to prolonging the time and maintaining safety throughout the procedure.